Threshold ring signature for wireless sensor networks - Jun-fang XIAO; Jian LIAO; Gui-hua ZENG (Tongxin xuebao)
Compared with traditional network,the wireless sensor nodes are limited in the storage,mobility,computation,energy,and so on.A threshold ring signature scheme suitable for wireless sensor networks based on bilinear pairings was proposed.Assuming the abstrusity of computational Diffie-Hellman problem,the secure proof was shown in the model of random oracles using the reduction to the contravention.Proposed scheme also had other characteristics,such as robustness,multi-signature and parallel computation.